Oaks: an evolutionary success story - Kremer, Antoine (New Phytol, 2019)
The genus Quercus is among the most widespread and species-rich tree genera in the northern hemisphere. The extraordinary species diversity in America and Asia together with the continuous continental distribution of a limited number of European species raise questions about how macro- and microevolutionary processes made the genus Quercus an evolutionary success. Synthesizing conclusions reached during the past three decades by complementary approaches in phylogenetics, phylogeography, genomics, ecology, paleobotany, population biology and quantitative genetics, this review aims to illuminate evolutionary processes leading to the radiation and expansion of oaks. From opposing scales of time and geography, we converge on four overarching explanations of evolutionary success in oaks: (1) accumulation of large reservoirs of diversity within populations and species; (2) ability for rapid migration contributing to ecological priority effects on lineage diversification; (3) high rates of evolutionary divergence within clades combined with convergent solutions to ecological problems across clades; and (4) propensity for hybridization, contributing to adaptive introgression and facilitating migration. Finally, we explore potential future research avenues, emphasizing the integration of microevolutionary and macroevolutionary perspectives.